DEMOKRASI DALAM FILSAFAT PENDIDIKAN BARAT DAN ISLAM (KAJIAN TENTANG NILAI-NILAI DEMOKRASI DAN IMPLEMENTASINYA DALAM KONTEKS PENDIDIKAN INDONESIA) - Mufiqur Rahman (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
Is there democracy in Islam?, how is the attitude of Muslims to democracy, is Islam compatible with democracy? This question gets a different reaction from Muslim thinkers. This means that Democracy in Islam is still a controversial issue, both theoretically and practically. There are at least two groups or blocks of views from Muslim thinkers. First the conservative group, they reject openly Islamic relations with democracy. For them in Islam there is no place for democracy. Second, the moderate Islamic view group. This group holds that the substance (essence) of democracy is in line with Islamic principles. While democracy in the view of Western educational philosophy in this paper is represented by the opinion of Dewey (1916/1996), Schumpeter (1942), Dahl (1971) and Zulu records (2001). While the view of democracy in the philosophy of Islamic education is represented by the view of moderate Islamic groups that bring Democracy into Islamic education in a dialogical way. The point is that the values of Democracy can be strengthened through education. Democracy and education are entities that can not be separated in achieving the two educational objectives as Nurcholis Madjid said in Indonesia context.